2022
DOI: 10.3389/fonc.2022.834749
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Galectin-1 but Not Galectin-3 in Patients With Lung Adenocarcinoma After Radiation Therapy

Abstract: IntroductionTo investigate the role of tumor galectin-1 and galectin-3 in patients with lung adenocarcinoma after definitive radiation therapy.MethodsA total of 41 patients with localized lung adenocarcinoma undergoing thoracic radiation therapy without concurrent chemotherapy were enrolled. Their paraffin-embedded lung tissues were sent for immunohistochemical staining for galectin-1 and galectin-3. The clinical treatment outcomes, including overall (OS), locoregional progression-free (LRPFS), and distant met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Abnormal galectin-1 levels correlated with decreased overall survival, as depicted in Figure 6 B with no difference for galectins-3 and -9 in Figure 6 C and Figure 6 D, respectively. The lack of differences observed for galectin-3 levels and the differences observed for galectin-1 levels correlate with previous studies [ 22 , 34 , 49 ]. It is of note that there was no difference in OS when galectin-1 levels were separated into low, normal, and high values, as seen in Figure 6 A, albeit it approached significance ( p = 0.0953).…”
Section: Discussionsupporting
confidence: 91%
“…Abnormal galectin-1 levels correlated with decreased overall survival, as depicted in Figure 6 B with no difference for galectins-3 and -9 in Figure 6 C and Figure 6 D, respectively. The lack of differences observed for galectin-3 levels and the differences observed for galectin-1 levels correlate with previous studies [ 22 , 34 , 49 ]. It is of note that there was no difference in OS when galectin-1 levels were separated into low, normal, and high values, as seen in Figure 6 A, albeit it approached significance ( p = 0.0953).…”
Section: Discussionsupporting
confidence: 91%
“…Abnormal galectin-1 level was associated with decreased overall survival as depicted in Figure 6b with no difference for galectins-3 and -9 in Figures 6c and 6d, respectively. The negative finding with galectin-3 and positive finding with galectin-1 correlates with previous trials [22,35,48]. However, these findings were further expanded upon with subsequent analysis highlighting that the difference stemmed from patients with NSCLC (Figure 7A) versus SCLC (Figure 7B).…”
Section: Resultssupporting
confidence: 80%
“…Galectin-1 (Gal1) is one of the 15 members of the beta-galactose-binding proteins, galactoagglutinins. Recent studies have demonstrated that Gal1 is expressed in a variety of malignant tumors, including hepatocellular carcinomas [ 7 ], lung adenocarcinomas [ 8 ], pancreatic cancers [ 9 ], breast cancers [ 10 ], colon cancers [ 11 ], and GC [ 12 ]. It is mainly distributed in the extracellular matrix and cytoplasm, and regulates various biological activities of cancer cells.…”
Section: Introductionmentioning
confidence: 99%